Construction of a three-level enteral nutrition nursing system under the “Internet + medical” mode and an evaluation of its effect in clinical application - Hu, Min; Ling, Yan; Xiong, Fang-Ting; Xu, Jian-Mei (Frontiers in Public Health, 2022)
Objective: This study aimed to explore the construction of a three-level enteral nutrition nursing system under the “Internet + medical” mode and the clinical application effect. Methods: A total of 40 nurses from four primary and secondary hospitals in Jiangxi Province and 100 patients treated with enteral nutrition between January 2020 and December 2021 were enrolled in this study. The patients were randomly divided into a control group and a study group, with 50 cases in each. Patients in the control group received routine enteral nutrition nursing. In the study group, a three-level enteral nutrition nursing system was applied under the “Internet + medical” mode to train and guide the implementation of clinical enteral nutrition. The changes in nurses’ cognition and behavior in enteral nutrition safety nursing, comprehensive core competence before and after training, and the effect of enteral nutrition nursing were compared between the two groups. Results: After three months of training, nurses’ cognition and behavior scores in enteral nutrition safety nursing were higher than those before training (t = 11.780, P < 0.05), and nurses’ core competence scores were higher than before training (P < 0.05). After one week of nursing, the nutritional risk screening 2002 (NRS2002) score decreased, and the levels of albumin and hemoglobin increased in both groups (P < 0.05). However, after one week of nursing, the NRS2002 score of the study group (2.89 ± 0.75) was lower than that of the control group (3.25 ± 0.82), and the levels of albumin (39.89 ± 3.21) and hemoglobin (119.57 ± 8.78) were higher in the study group than in the control group (albumin 36.25 ± 3.45, hemoglobin 113.66 ± 9.55) (P < 0.05). Conclusion: Three-level enteral nutrition nursing linkage assisted by the “Internet + medical” mode can improve the cognition and behavior of medical staff in enteral nutrition safety nursing, as well as the comprehensive core competence of nurses, achieving good clinical effects.